The prediction of potential energy and matter production from biomass pyrolysis with artificial neural network - Bahattin Aydinli; Atila Caglar; Sefa Pekol; Abdulkadir Karaci (SAGE Publications, 2017)
The potentiality determination of renewable energy resources is very important. The biomass is one of the alternative energy and material resources. There is great effort in their conversion to precious material but yet there is no generalized rule. Therefore, the prediction of the energy and material potentials of these resources has gained great importance. Also, the solution to environmental problems in real time can be found easily by predicting models. Here, the basic products of pyrolysis process, char, tar and gas were also predicted by artificial neural network modelling. The half of data obtained from real experimental process along with some content and proximate analysis were fed into artificial neural network modelling. After the training of the model with this data, the remaining half of the data were introduced into this artificial neural network model. And the model predicted the pyrolysis process products (char, tar and gaseous material). The predicted data and the real experimental data were compared. In addition, another aim of this study is to reduce the labour in identification and characterization of the pyrolysis products. For this purpose, a theoretical framework has also been sketched. The necessity of a generalized rule for generation of energy and matter production from biomass pyrolysis has been punctuated. As a result, the ANN modelling is found to be applicable in the prediction of pyrolysis process. Also, the extensive reduction in labour and saving in economy is possible.
Keywords: TK1001-1841; Production of electric energy or power. Powerplants. Central stations; TJ807-830; Renewable energy sources; 13. Climate action; 7. Clean energy